SERAPAN HARA TANAMAN KAYU KUKU (Pericopsis mooniana Thw.) BERMIKORIZA PADA INTERVAL PENYIRAMAN BERBEDA: Nutrient Uptake of Pericopsis mooniana Thw. with Mikoriza on Different Watering Intervals - Husna; Faisal Danu Tuheteru; Al Basri; Asrianti Arif; Basruddin; Yuningsih Umar (HUTAN TROPIKA, 2020)
The aim of the study was to determine the effect of a combination of mycorrhizal fungi and watering intervals on kayu kuku (Pericopsis mooniana) grown on gold tailings media. This research was conducted at the green house of the Indonesian Mycorrhizal Association (AMI) Southeast Sulawesi branch for 4 months (March-July 2019). The study used a factorial randomized block design (CRD) with two factors being tested, the first factors including no AMF inoculation, using Claroideoglomus etunicatum and Septoglomus constrictum which were given 10 grams each. The second factor included watering every day, every two days and every three days, with three replications and three crop units. The results showed that the treatment combination of AMF type S. constrictum with daily watering intervals increased P nutrient levels on the shoot and root, while three days watering intervals increased Mn uptake on the shoot. The combination of AMF treatment for C. etunicatum and daily watering intervals increased the Mn level of the roots and the two days watering interval increased the P uptake on the shoots and roots. The best treatment was a combination of AMF type C. etunicatum and two days watering intervals which effectively increased P uptake of the shoot. Independently, AMF treatment for S. constrictum and two days watering interval were effective in increasing the levels and P nutrients uptake on the shoot. Keywords: Drought stress, Arbuscular Mycorrhizal Fungi, Pericopsis mooniana, uptakeof nutrients.